2012
DOI: 10.1063/1.4725413
|View full text |Cite|
|
Sign up to set email alerts
|

Charge transfer equilibria in ambient-exposed epitaxial graphene on (0001¯) 6 H-SiC

Abstract: The transport properties of electronic materials have been long interpreted independently from both the underlying bulk-like behavior of the substrate or the influence of ambient gases. This is no longer the case for ultra-thin graphene whose properties are dominated by the interfaces between the active material and its surroundings. Here, we show that the graphene interactions with its environments are critical for the electrostatic and electrochemical equilibrium of the active device layers and their transpo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
46
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(47 citation statements)
references
References 32 publications
1
46
0
Order By: Relevance
“…This behavior is consistent with previous results on epitaxial graphene on SiC 6, 16 . The change in N s from air exposure can be explained by a redox reaction at the surface of the graphene involving various environmental gases, which results in electron withdrawal 5 . Exposure to an inert gas, such as nitrogen or helium, is thought to cause the doping agents at the graphene surface to desorb, which reverses the electron withdrawal.
Figure 2Best-match model results for sheet carrier density N s and mobility μ as a function of time.
…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This behavior is consistent with previous results on epitaxial graphene on SiC 6, 16 . The change in N s from air exposure can be explained by a redox reaction at the surface of the graphene involving various environmental gases, which results in electron withdrawal 5 . Exposure to an inert gas, such as nitrogen or helium, is thought to cause the doping agents at the graphene surface to desorb, which reverses the electron withdrawal.
Figure 2Best-match model results for sheet carrier density N s and mobility μ as a function of time.
…”
Section: Resultsmentioning
confidence: 99%
“…2 is an ambient acceptor doping redox reaction at the graphene surface involving O 2 , H 2 O, and CO 2 5 . To summarize this previously proposed mechanism, first thin films of water form at surfaces when exposed to ambient.…”
Section: Resultsmentioning
confidence: 99%
“…35,[42][43][44][45][46][47][48] Furthermore, humidity enhances hole doping by O 2 . 49 Sque et al specifically suggested that graphene could undergo transfer doping to the aqueous oxygen redox couple.…”
Section: Discussionmentioning
confidence: 99%
“…A similar absolute value of Seebeck coefficient was found for single layer graphene made by chemical vapor deposition on Cu (6 lV/ C) 28 or for multilayer epitaxial graphene on Si (À30 lV/ C). 29 It should be stressed here that the Seebeck coefficient can show different values (from 6 lV/ C to 180 lV/ C) and depends highly on the method of sample preparation, measurements method, sample thickness, etc. 30 …”
Section: -4mentioning
confidence: 99%